Divorced Parents: Communication Privacy Management of Family Issues Among Generation Z - Felicia Susanto; Santoso, Nobertus Ribut (Fakultas Ilmu Komunikasi Universitas dr. Soetomo, 2025)
The divorce cases, giving psychological impacts on children, significantly increase year. study explores the complex process of information disclosure and privacy management among Generation Z individuals as they share sensitive information about family breakups with significant others. By employing a case study method of qualitative approach, this study gathered the data through in-depth interviews with five Generation Z participants from families that have experienced divorce and it was deductively analyzed. The study reveals that Generation Z individuals perceive a strong sense of ownership of information over the details of their parent's divorce, emphasizing the need to control the information and assessing the risk-benefit ratio of disclosing divorced parents. Participants also demonstrate the use of privacy rules to guide their disclosure decisions, highlighting their desire to protect both their privacy and their relationships with significant others. These privacy rules are employed repeatedly, shaping their basic orientations toward privacy choices and reflecting the dynamic interplay between the need for privacy and the desire for social connection. The study underscores the importance of understanding these privacy management strategies when developing interventions aimed at supporting Generation Z individuals in sharing difficult family news. By acknowledging the nuanced ways in which they navigate disclosure, mental health professionals, educators, and policymakers can better support Generation Z individuals in maintaining their well-being while managing the challenges of sharing personal information in an interconnected world.